Mathematical Knowledge of Fala Foka by The Takpala Indigenous People - Andrian Runtius Lalang; Florianus Aloysius Nay (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
ala foka is a warehouse and dwelling house of the Abui tribe who live in Takpala Traditional Village. In the construction of this house there is mathematical knowledge. This mathematical knowledge in the construction of fala foka can also be called ethnomathematics. This study aims to explore the mathematical knowledge contained in the construction of fala foka. Data collection methods include documentation, observation and interviews with indigenous people and teachers. The sources were obtained using snowball sampling. The results of this study are in the form of base 25 numbers in reed ties, geometry in the form of triangles and lines on the vertices, geometry in the form of rectangular pyramids on the roof of fala foka, geometry in the form of triangles on the roof shape, rectangles on the pelupu and dilation knowledge on the floor of each level of fala foka, the concept of rectangular area on the pelupu.